I need the actual problem to answer this question
Answer:
18
Step-by-step explanation:
Answer:
Simplifying
x2 + -4y2 = 25
Solving
x2 + -4y2 = 25
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4y2' to each side of the equation.
x2 + -4y2 + 4y2 = 25 + 4y2
Combine like terms: -4y2 + 4y2 = 0
x2 + 0 = 25 + 4y2
x2 = 25 + 4y2
Simplifying
x2 = 25 + 4y2
Reorder the terms:
-25 + x2 + -4y2 = 25 + 4y2 + -25 + -4y2
Reorder the terms:
-25 + x2 + -4y2 = 25 + -25 + 4y2 + -4y2
Combine like terms: 25 + -25 = 0
-25 + x2 + -4y2 = 0 + 4y2 + -4y2
-25 + x2 + -4y2 = 4y2 + -4y2
Combine like terms: 4y2 + -4y2 = 0
-25 + x2 + -4y2 = 0
The solution to this equation could not be determined.
Step-by-step sorry if im wrong
9514 1404 393
Answer:
C. 78°
Step-by-step explanation:
The sum of angles in a triangle is 180°.
(7x-6)° +(4x+11)° +43° = 180°
11x +48 = 180 . . . . . divide by °, simplify
11x = 132 . . . . . . . subtract 48
x = 12 . . . . . . . divide by 11
Then the measure of angle T is ...
∠T = (7x -6)° = (7(12) -6)°
∠T = 78°
Answer:
The point is (2,-2)
Explanation: